Pendidikan Damai sebagai Pembinaan Keadabaan Kewarganegaraan di Bidang Sosial - Zuhri Zurgobban (MODELING: Jurnal Program Studi PGMI, 2016)
This research aims to describe the impact of peace education program carried out by Peace Generation community as an attempt to develop the civic virtue in the social field. Research method used is a case study with qualitative approach. The research subject are including community administrator, tutor implementers, and attendees program. In the collecting data, the techniques used observation, interviews, and documentation. Data were analyzed using data reduction, data presentation and conclusion/verification. The result of this research show that this program can improve social intelligence and creating civic participation in preventing and combating social problems that ultimately citizens building character and personality to have responsibility in social life.